Modelowanie warunków pracy pompowni w systemach grawitacyjno-tłocznych = Modeling of pump operation conditions in gravity-pressure combined systems - Nowogoński, Ireneusz; Ogiołda, Ewa; Kubiszyn, Marlena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the problem of working conditions in gravitational pressure systems simulation. The practical example takes into account the dynamical analysis of a system equipped with 10 pump stations with different functions. Both local press stations, local stations for shallowing network and transit pumping stations between the towns were used. The model allowed to optimize the active volume of the pump station tanks, the selection of pumps, including the frequency of power on and the time of holding the sewage.
Keywords: pompownia kanalizacyjna; systemy grawitacyjno-tłoczne; lokalne punkty tłoczne; pompownie tranzytowe; pompy; symulacja; sewage pumping stations; gravity-pressure systems; modeling